2010
DOI: 10.1089/cell.2009.0097
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Inhibitory Factor (LIF) Enhances Germ Cell Differentiation from Primate Embryonic Stem Cells

Abstract: Recently, several research groups have shown that germ cells can be produced in vitro from pluripotent embryonic stem cells (ESCs). In the mouse, live births of offspring using germ cells induced from ESCs in vitro have been reported. Furthermore, some efficient methods for inducing the useful number of germ cells from ESCs have also been developed. On the other hand, in primates, despite the appearances of germ cell-like cells including meiotic cells were observed by spontaneous differentiation or introducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…LIF with VEGF maintained the preliminary, progenitor phenotype of EPCs LIF is a key cytokine in stem cell biology and combining with other growth factors, it upregulates embryonic germ (EG) colony number (Fukunaga et al, 2010;Tee et al, 2010). VEGF is the most important cytokine in EPCs and could increase EPC number and enhance proliferation in a dose-dependent manner (Fujinaga et al, 2009;Xiao-Yun et al, 2011;Zhou et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…LIF with VEGF maintained the preliminary, progenitor phenotype of EPCs LIF is a key cytokine in stem cell biology and combining with other growth factors, it upregulates embryonic germ (EG) colony number (Fukunaga et al, 2010;Tee et al, 2010). VEGF is the most important cytokine in EPCs and could increase EPC number and enhance proliferation in a dose-dependent manner (Fujinaga et al, 2009;Xiao-Yun et al, 2011;Zhou et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The differentiation can be enhanced by conditioned medium from testicular or ovarian cells or by adding recombinant BMP4, RA or SCF (76). The self-renewal of differentiated PGC-like cells can be prolonged by LIF treatment (77). Further studies, including functional assays in vivo, would be interesting to examine their developmental potential and molecular mechanisms of primate germline development as a substitute model for human germ cell differentiation from pluripotent stem cells.…”
Section: Germline Differentiation From Non-human Primate Es/ipscsmentioning
confidence: 99%
“…First, human PSCs were differentiated into SSC-like cells, cells that reside at the foundation of spermatogenesis. Several previous studies have shown the ability of human and non-human primates PSCs to differentiate into PGCs [3,17,29,44,45,55,56,62]. Although this cell lineage has the capability of restoring fertility in rodents, including primordial germ cells (PGCs) derived from mouse PSCs [6,20], SSCs remain the gold standard for colonizing cells which recapitulate spermatogenesis following transplantation [1,27].…”
Section: Discussionmentioning
confidence: 99%